Proceedings of IEEE Symposium on Computer-Based Medical Systems (CBMS)
DOI: 10.1109/cbms.1994.316016
|View full text |Cite
|
Sign up to set email alerts
|

A new, robust vocal fundamental frequency (F/sub 0/) determination method for the analysis of infant cries

Abstract: The extraction and analysis of the fundamental frequency ( Fo) of infant vocalizations has been the focus of a number of efforts over the past thirty years. It is thought that this parameter is an important information channel from which information regarding the state of an infant can be determined. To date, research groups working to extract the vocal fundamental frequency of infant cries have been limited in the resolution and granularity of the Fo extraction methods used for adult speech, which, typically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The two‐month‐olds were totally unsurprised by the jack‐in‐the‐box, and very few infants cried in all three conditions, although enough to analyze. There was a pain cry which was high pitched, long in duration, and dysphonated, which is heard as harsh 4,5 …”
Section: Measuring Pain In Nonverbal Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two‐month‐olds were totally unsurprised by the jack‐in‐the‐box, and very few infants cried in all three conditions, although enough to analyze. There was a pain cry which was high pitched, long in duration, and dysphonated, which is heard as harsh 4,5 …”
Section: Measuring Pain In Nonverbal Patientsmentioning
confidence: 99%
“…There was a pain cry which was high pitched, long in duration, and dysphonated, which is heard as harsh. 4,5 However, I had wandered from the initial request about infants in the NICU, the ones undergoing numerous painful procedures, as opposed to healthy infants receiving an injection every two months.…”
Section: Me a Suring Pain In Nonverbal Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bloom et al (1999) calculated frequency-amplitude slopes in preverbal syllabic sounds as a measure of nasality. In addition, the fundamental frequency (F0), i.e., the lowest frequency of vocal fold oscillation, has always been a frequently extracted featurein voice analytics in general, but also for acoustic preverbal sound characterization (e.g., Keating and Buhr 1978;Kent and Murray 1982;Petroni et al 1994;Robb et al 1989). A number of recent studies on crying vocalizations also reported on F0-related preverbal atypicalities in individuals with ASD (e.g., Esposito and Venuti 2010;Esposito et al 2013;Sheinkopf et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other sign may be present in the first month of life such as dry, cold and pale skin, feeding difficulty, insufficient weight gain, noisy breathing, nasal congestion, respiratory disorders, obstipation and lethargy. [1] Newborn infant cry is characterized by very high fundamental frequency (F 0 ) with abrupt changes and voiced or unvoiced features of very short duration, within a single utterance [2]. Vocal tract resonance frequencies are highly varying and to be tracked accurately.…”
Section: Introductionmentioning
confidence: 99%